Detection without further processing or processing without automatic detection? Differential ERP responses to lexical-semantic processing in toddlers at high clinical risk for autism and language disorder. (August 2021) - Cantiani, Chiara; Riva, Valentina; Dondena, Chiara; Riboldi, Elena Maria; Lorusso, Maria Luisa; Molteni, Massimo
Abstract: Delays in early expressive vocabulary can reflect a specific delay in language acquisition or more general impairments in social communication. The neural mechanisms underlying the (dis)ability to establish the first lexical–semantic representations remain relatively unknown. Here, we investigate the electrophysiological underpinnings of these mechanisms during the critical phase of lexical acquisition in two groups of 19-month-old toddlers at risk for neurodevelopmental disorders, i.e., children characterized by low expressive vocabulary (late talkers, N = 18) and children with early signs of Autism Spectrum Disorder (ASD, N = 18) as compared to typically developing children (N = 28), with the aim to identify similarities and specificities in lexical-semantic processing between these groups. ERPs elicited by words (either congruous or incongruous with the previous picture context) and pseudo-words are investigated within a picture-word matching paradigm. In order to further interpret ERP responses, we look at longitudinal intra-group associations with language and socio-communications skills at age 24 months. As expected, we found differences between the groups that might underlie specificities, but also similarities. On the one side, late talkers differed from the other two groups in the early component (phonological-lexical priming effect) reflecting detection of the correspondence between the heard word and the lexical representation pre-activated by the picture. On the other side, children with early symptoms of ASD differed from the other two groups in the late component (late positive component) reflecting the effortful semantic re-analysis following a violation. The functional interpretation of the two components is corroborated by significant correlations suggesting that the early component is associated with later socio-communication skills, whereas the late component is associated with linguistic skills. Results point in the direction of differential impaired mechanisms in the two populations, i.e., impaired automatic detection of incongruencies in late talkers vs. absence of high-level re-analysis of such incongruencies in children with early signs of ASD.